Macrophage Migration Inhibitory Factor Promotes the Interaction between the Tumor, Macrophages, and T Cells to Regulate the Progression of Chemically Induced Colitis-Associated Colorectal Cancer - Thalia Pacheco-Fernández; Imelda Juárez-Avelar; Oscar Illescas; Luis I. Terrazas; Rogelio Hernández-Pando; Carlos Pérez-Plasencia; Emma B. Gutiérrez-Cirlos; Federico Ávila-Moreno; Yolanda I. Chirino; José Luis Reyes; Vilma Maldonado; Miriam Rodriguez-Sosa (Hindawi Limited, 2019)
Colitis-associated colorectal cancer (CRC) development has been shown to be related to chronically enhanced inflammation. Macrophage migration inhibitory factor (MIF) is an inflammatory mediator that favors inflammatory cytokine production and has chemotactic properties for the recruitment of macrophages (Møs) and T cells. Here, we investigated the role of MIF in the inflammatory response and recruitment of immune cells in a murine model of chemical carcinogenesis to establish the impact of MIF on CRC genesis and malignancy. We used BALB/c MIF-knockout (MIF-/-) and wild-type (WT) mice to develop CRC by administering intraperitoneal (i.p.) azoxymethane and dextran sodium sulfate in drinking water. Greater tumor burdens were observed in MIF-/- mice than in WT mice. Tumors from MIF-/- mice were histologically identified to be more aggressive than tumors from WT mice. The localization of MIF suggests that it is also involved in cell differentiation. The relative gene expression of il-17, measured by real-time PCR, was higher in MIF-/- CRC mice, compared to the WT CRC and healthy MIF-/- mice. Importantly, compared to the WT intestinal epithelium, lower percentages of tumor-associated Møs were found in the MIF-/- intestinal epithelium. These results suggest that MIF plays a role in controlling the initial development of CRC by attracting Møs to the tumor, which is a condition that favors the initial antitumor responses.